Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasan Masyarakat Dalam Pembuatan Kartu Tanda Penduduk Elektronik (E-Ktp) Di Kelurahan Tugu Utara Jakarta Utara - Ranti Damaiyanti; Ayu Pratiwi Paramitha (Jurnal Ilmu Administrasi Publik, 2025)
This study aimed to determine the Effect of Service Quality and Facilities on Community Satisfaction in Making Electronic Identity Cards (E-KTP) in Tugu Utara, North Jakarta. This research used a quantitative approach. The analysis method used in this research is multiple linear regression analysis using the help of the SPSS version 27 program. The data research was collected through observation, questionnaires, and literature studies, regression methods, correlation T test and F test were used to analyse it. The results of research on the effect of Service Quality positively and significantly on Public Satisfaction in Making Electronic Identity Cards (E-KTP) in Tugu Utara Village with the coefficient of determination showed R square (r2) and the amount of influence is 0.345 or 34.5% and the remaining 65.5% is influenced by other factors not examined. There is a positive and significant effect of facilities on public satisfaction in making electronic identity cards (E-KTP) in Tugu Utara Village with the coefficient of determination showing R square (r2) and the amount of influence is 0.532 or 53.2%. and the remaining 46.8% is influenced by other factors not examined. There is a positive and significant effect of service quality and facilities on community satisfaction with the coefficient of determination showing R square (r2) and the amount of influence is 0.559 or 55.9% and the remaining 44.1% is influenced by other factors not examined. The test results shown by the calculated F score are 61,600 while the amount of F table with a free degree (df) of 3 and 100 at (0.05) is 2.70. Thus, the value of F score (61.600) > F table (2.70). This means that H0 is rejected and consequently H3 is accepted. Keywords Quality of Service and Facilities to Community Satisfaction